Cenozoic volcanism in the Tyrrhenian Sea Region - Peccerillo, Angelo (Advances in volcanology., 2017)
This is an updated edition of the book by the same author: "Plio-Quaternary volcanism in Italy - Petrology, geochemistry, geodynamics," published in 2005 by Springer. This edition has the same structure as the previous publication, with a general introduction; various chapters dedicated to different volcanic provinces in Italy; and a final chapter on the relationships between magmatism and geodynamics. It includes information that has become available in the last ten years, and new chapters have been added offering detailed discussions of the Oligo-Miocene orogenic volcanism on Sardinia and of some small outcrops of fragmented volcanic rocks occurring in several places of the Apennines. This new edition now covers the entire Tyrrhenian Sea magmatism of the last 40 Ma. Lastly, it includes two appendices: Appendix 1 is an update of the 2005 edition appendix. Appendix 2 discusses the basic principles of igneous petrology, trace elements and isotope geochemistry, providing geoscientists unfamiliar with petrology-geochemistry insights into how major trace elements and isotopic data on volcanic rocks allow a better understanding of magmatism and geodynamics.- Resumé vydavatel